2018
DOI: 10.1063/1.5038828
|View full text |Cite
|
Sign up to set email alerts
|

Fast ion D-alpha measurements using a bandpass-filtered system on EAST

Abstract: Based on the charge exchange reaction between fast ions and a neutral beam, fast ion features can be inferred from the spectrum of Doppler-shifted Balmer-alpha light from energetic hydrogenic atoms. In order to study the interaction between instabilities and fast-ion transport, recently we extended the fast ion D-alpha (FIDA) measurements by using a combination of a bandpass filter and a photomultiplier tube (PMT) (f-FIDA). A bandpass filter selects the desired spectral band from 651 nm to 654 nm before detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that reconstructing the velocity distribution function from a diagnostic system with incomplete coverage of velocity space is a challenging task [7,11,[14][15][16]. Specifically at the EAST tokamak, the two-view FIDA diagnostic [17,18] is sensitive to fast ions in substantial regions of velocity space, but leave other regions covered by only one view [19]. To nevertheless enable reliable reconstructions of the fast-ion distribution from sparse datasets, a palette of prior information has been developed [14,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that reconstructing the velocity distribution function from a diagnostic system with incomplete coverage of velocity space is a challenging task [7,11,[14][15][16]. Specifically at the EAST tokamak, the two-view FIDA diagnostic [17,18] is sensitive to fast ions in substantial regions of velocity space, but leave other regions covered by only one view [19]. To nevertheless enable reliable reconstructions of the fast-ion distribution from sparse datasets, a palette of prior information has been developed [14,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding fast-ion behaviour and related physical issues is a critical aspect to achieve the EAST scientific objectives. Accordingly, several complementary fast-ion measurements [13,14] have been developed and validated on EAST, e.g. fast-ion D-alpha (FIDA), fast-ion loss detectors (FILDs), neutral particle analysers (NPA), neutron flux monitor and TOFED neutron spectrometers.…”
Section: Introductionmentioning
confidence: 99%
“…They can also drive instabilities, which can act on specific parts of the fast-ion velocity-space distribution, causing anomalous fast-ion redistribution and loss [2] potentially resulting in damage to the components on the first wall. To obtain information about fast-ion velocity-space distribution function, fast-ion D-alpha (FIDA) measurements [3,4] are commonly used in tokamak and stellarator devices, such as DIII-D [5], LHD [6], NSTX [7], ASDEX Upgrade [8], TCV [9], MAST [10], experimental advanced superconducting tokamak (EAST) [11,12]. The principle of the FIDA diagnostic is that the neutralized fast ions, resulting from chargeexchange reactions, are in excited states and emit Balmeralpha radiation with a Doppler shift that is dependent on the fast-ion velocity.…”
Section: Introductionmentioning
confidence: 99%